VARIASI KONSENTRASI KARBOPOL 940 PADA FORMULASI NANOEMULGEL EKSTRAK ETANOL 96% DAUN JAMBU BIJI Psidium guajava L - Rakhmi Hidayati; Nining Febri Muzdalifah; Gendis Purno Yudanti (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Background : Guava leaves contain flavonoid, terpenoid, tannin and saponin compounds. Nanoemulgel is formulated from nanoemulsion incorporated into a gelling agent so that when applied topically with small particle size it will penetrate inti the skin better. Objective : to determine the physical characteristics and the best forua of nanoemulgels preparation of 96% ethanol extract of guava leaves with variations in carbopol 940 concentration. Method :The study began with the manufacture of nanoemulsion and critical parameter tests were carried out including particle size, zeta potential and percent transmittance. Nanoemulsion was then incorporated into the nanoemulgel formula with 3 variations of carbopol 940 concentration, namely 0,5%, 0,75% and 1%. The physical test parameters carried out were organoleptic tests, homogeneity tests, pH, spreadability, adhesion and viscosity. Result : the critical parameter test of nanoemulsion showed a particle size value of 89,95 nm, a zeta potential of -2,97 mV and a transmittance percentage of 09,6%. Tween 80, PEG 400 and VCO had a good effect on the physical properties of nanoemulsion. Conclusion : the physical properties test of nanoemulgel showed that differences in the concentration of carbopol 940 as a gelling agent did not have a significant effect on organoleptic tests, homogeneity tests, pH, spreadability and viscosity. Variations in the concentration of carbopol 940 1% was the best concentration to obtain the best physical characteristics of nanoemulgel